Emblica officinalis Irrigation as an Adjunct to Scaling and Root Planing: A Randomized Controlled Clinical Trial - Tewari, Shika; Grover, Shilpa; Sharma, Rajinder K; Singh, Gajendra; Sharma, Anuradha (UI Scholars Hub, 2018)
Objective: To evaluate the effect of 10% Emblica officinalis irrigation, which has anti-inflammatory, antioxidative, and antimicrobial activities, adjunctive to scaling and root planing (SRP) for treatment of chronic periodontitis. Methods: Sixty-six patients were randomly assigned to the negative control group (SRP+saline irrigation; n=22), positive control group (SRP+chlorhexidine irrigation; n=22), and test group (SRP+10% E. officinalis irrigation; n=22). Plaque index (PI), gingival index (GI), probing pocket depth (PPD), clinical attachment level (CAL), and sulcus bleeding index (SBI) were monitored ≤3 months post-therapy. Results: There were significantly greater reductions in the mean PI, PPD, and SBI but a greater mean CAL at 3 months post-therapy in the test group than in the negative control (p<0.05). Compared with the positive control, the test group demonstrated greater reduction in SBI but comparable improvements in PI, GI, CAL, deep pockets (PPD≥5–6 mm, ≥7 mm), and sites with CAL ≥6 mm at 3 months post-therapy (p>0.05) but less reduction in the mean PPD (p<0.05). Conclusions: E. officinalis 10% irrigant adjunctive to SRP improved periodontal healing without side effects and may be an alternative to chlorhexidine for chronic periodontitis treatment.